2019
DOI: 10.1111/jpi.12565
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin pharmacokinetics and dose extrapolation after enteral infusion in neonates subjected to hypothermia

Abstract: Introduction Neonates with hypoxic‐ischemic encephalopathy (HIE) undergoing hypothermia may benefit from adjunctive therapy with melatonin. However, melatonin safety, pharmacokinetics (PK), and dosage in this sensitive population are still unknown. Methods and results This study assessed the PK and safety of melatonin enteral administration to neonates with HIE undergoing hypothermia. Melatonin was infused at 0.5 mg/kg in five neonates with HIE undergoing hypothermia. Infusion started 1 hour after the neonates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 32 publications
1
53
0
2
Order By: Relevance
“…It is feasible that in babies with NE, resuscitation would be completed and venous access in place by 1 h, enabling the start of melatonin infusion. Oral melatonin has been used in NE babies undergoing HT and is absorbed 33,34 , however for rapid achievement of therapeutic levels and optimal protection, intravenous administration is more reliable. In the piglet model we have observed that brain protection is dependent on the time after HI that therapeutic levels are achieved 14 .…”
Section: Discussionmentioning
confidence: 99%
“…It is feasible that in babies with NE, resuscitation would be completed and venous access in place by 1 h, enabling the start of melatonin infusion. Oral melatonin has been used in NE babies undergoing HT and is absorbed 33,34 , however for rapid achievement of therapeutic levels and optimal protection, intravenous administration is more reliable. In the piglet model we have observed that brain protection is dependent on the time after HI that therapeutic levels are achieved 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Brain or whole-body hypothermia is currently the only therapeutic option offering amelioration in the prognosis, as from preclinical and clinical data [26,[43][44][45]. In addition, evidence of a benefit from adjunctive therapy with melatonin has been described [46,47], and a recent study on melatonin safety, pharmacokinetics (PK), and dosage in the neonatal population reported positive results [25]. Finally, it is worth noting that a significant increase of melatonin was described following hypoxia both in experimental models and in human stroke, suggesting even the existence of an endogenous protective response on its part [48].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly relevant is the beneficial potential of melatonin in perinatal hypoxia. Melatonin has been previously used in association with the standard hypothermic therapy in newborns affected by hypoxia, with positive results [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Since melatonin is mainly metabolized by cytochrome P450 (CYP) 1A2 and CYP2C19, inhibitors of these enzymes lead to higher concentration of melatonin in the body [42]. Melatonin lowers blood pressure and glucose level, therefore, patients receiving antihypertensive or blood glucose lowering drugs should use melatonin with cautious [43]. Since the administration of melatonin during pregnancy is not studied, its use is not recommended for pregnant women [38].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, melatonin elimination occurs faster in children in comparison to adults [54]. Low absorption from the gastrointestinal tract, high first-pass effect and high rate of metabolizing make melatonin a drug with low [43,55].…”
Section: Introductionmentioning
confidence: 99%